Mechanism of bubble nucleation in poly(ε-caprolactone) foaming at low temperature. (19th November 2015) - Wang, Linyan; Zhou, Hongfu; Wang, Xiangdong; Mi, Jianguo
Abstract: CO2 bubble nucleation on the microrough poly(ε-caprolactone) surface has been investigated using a density functional theory approach. For the considered system, the effect of chemical and morphologic characteristics of poly(ε-caprolactone) on the solubility, surface tension, interfacial density distribution, nucleation free-energy barrier, and critical nucleus radius have been calculated to interpret the nucleation mechanism. All calculations are performed with the universal force field parameters. Some results have been examined by the available experimental data. According to the free-energy barrier and critical radius, the nucleation number with respect to pressure has been estimated under the instant depressurization. As a result, this work provides a theoretical explanation of bubble formation mechanism of polymer foaming at low temperature. Graphical abstract: Highlights: Consider the influence of morphology and attractive force of microrough PCL surface on the CO2 bubble nucleation. The free-energy contains the full information of the gas–liquid–solid three phase contacts. The predicted solubilities, surface tensions and nucleation number are close to the available experimental values. Systematical analysis of bubble nucleation mechanism during PCL foaming.